NAMA, MAKNA DAN IDENTITAS KOMUNITAS ADAT KAJANG DI SULAWESI SELATAN - Wahyuddin, Wahyuddin; Bandu, Irianti; Rahman, Nurhayati; Machmud, Mukarramah (JURNAL ILMU BUDAYA, 2023)
This article discusses the role of name in the society. Refuting the linguistic and the philosophy of language view that consider name serves only to designate or to distinguish one person from another, from the ethnological research, it is learnt that name represent culture. It reveals the cultural values and the dynamics of intercutultural interaction of a community. Through the naming practices in Kajang, a Makassar sub-ethnic, it is revealed that name is not only artificial feature but essential one. Mentioning a name in appropriate manner is considerd to invite the danger. Also, the preference of the name used show that while Kajang community is largely viewed as a traditional community, opposing to the modernity and other feature from outside, actually they have absorbed and adopted partly the Islamic values.